Simulation of a robot machining system based on heterogeneous-resolution representation. Issue 1 (2nd January 2016) - Chen, Yonghua; Wei, Ying
ABSTRACT: Collision avoidance is a frequently encountered problem in machining processes, especially in robot-based machining. In a robot machining system, collision may occur between the robot arm, the tool, tool holder and the work piece together with its fixtures. Therefore, a precise collision detection algorithm is critical to ensure that the tool path is collision free, particularly in the area where the tool has contact with the work piece. To verify tool paths, a simulation system is developed. In the proposed system, the robotic system is modeled as a Constructive Solid Geometry (CSG) tree where the Denavit-Hartenberg (D-H) notation is applied to represent the robot arm transformation matrix. A combined CSG representation and STereoLithography (STL) representation, the so called heterogeneous-resolution method is proposed to represent the work piece. By heterogeneous-resolution, the area of the work piece near the current machining contact point is represented by triangular facets at a controlled accuracy whereas other parts of the work piece are described by grid height array (GHA) to save computation time in order for the simulation to have less latency. When a collision is detected for a given cutter contact point, both the cutter location and the robot arm position are modified. The proposed method is implemented into a simulation software where the feasibility of the algorithm is tested and verified. GRAPHICAL ABSTRACT: